Theoretical Model of Neurotransmitter Release during In Vivo Vesicular Exocytosis Based on a Grainy Biphasic Nano-Structuration of Chromogranins within Dense Core Matrixes. Issue 4 (1st January 2016) - Oleinick, Alexander; Hu, Ren; Ren, Bin; Tian, Zhong-Qun; Svir, Irina; Amatore, Christian
Abstract : Exocytosis from dense core vesicles is an important ubiquitous process by which neurotransmitters are released from many cells. This has stimulated strong efforts to monitor and understand vesicular release events in order to infer their biological and physicochemical mechanisms. Though much has been achieved so far, many experimental observations remain unexplained, even puzzling, essentially because they envision that the vesicle matrixes consist of a homogeneous polyelectrolytic condensed phase encapsulated by the vesicles membranes. This work discloses a new model of dense core matrixes based on the physics of polyelectrolytes involving long chains of anionic moieties (here, chromogranins) condensed by a mixture of bulky monocations and small dications (here, catecholamines and calcium ions). It follows that matrixes cannot be homogeneous but necessarily consist of a dispersion of tightly compacted nano-grains immersed in a less condensed phase involving loosely folded chromogranin strands in which catecholamine cations may diffuse at significant rates. Even if such pomegranate-like description has to remain essentially theoretical up to when direct experimental means of testing is available, it leads to a whole set of predictions that are fully coherent with all experimental observations based on amperometric monitoring of vesicular exocytosis including some recent extremely puzzling ones.